Cross-CRP Analysis of Gender and Youth in the 2017-2022 CRP2 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
As part of its assessment of the CGIAR Research Program Portfolio (CRP2) submitted in March 2016, the Independent Science and Partnership Council (ISPC) commissioned two external reviews of gender and youth strategy in the 12 CRP and three platform proposals. This brief provides a summary of those external reviews. The reviews assessed the significance of research to the CGIAR Strategy and Results Framework’s (SRF) gender-related Intermediate Development Outcomes (IDOs) and sub-IDOs, and how gender and youth issues were considered in each proposal’s theory of change, impact pathway, work plan, and monitoring and evaluation approaches at the CRP, platform, and portfolio levels.